(untitled) (Journal of Applied Business and Economics, 2023)
This study utilized a data envelopment analysis model to study the performance persistence of 16 asset management institutions. When we evaluate performance based on capital efficiency (or productivity) ratio, earnings before interest, taxes, depreciation, and amortization (EBITDA) margin, and return on investment (ROI), we find that only one asset management bank has consistently outperformed its peers every year from 2014 to 2019. When we add tax efficiency, as measured by calculated tax rate, in addition to EBITDA, ROI, and capital efficiency ratio, we find that only 3 banks have consistently outperformed their peers in the industry every year for the period ranging from 2014 to 2019. These consistent findings indicate that, indeed, the skill of asset managers does play a role in asset management, at least in the short run.